Analisis Faktor-Faktor yang Mempengaruhi Tingkat Pengangguran Terdidik di Provinsi Jambi - Rosalina Rosalina; Purwaka Hari Prihanto; Erni Achmad (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2017)
This research aims to analyze the development of educated unemployment rates, education rate, economic growth, employment Rate and wages in Jambi Province and analyzed the effect of education rate, economic growth, employment rate and wages on the educated unemployment rate in Jambi Province. The data used is time series data from 2001-2016. This study uses descriptive analysis methods and quantitative analysis. The results showed that partially education rate and employment rate positive and significant influence on the educated unemployment rate in Jambi Province. While economic growth and wages has no effect on the educated unemployment rate in Jambi Province. Simultaneously the education rate, economic growth, employment rate and wages have a significant influence on the educated unemployment rate in Jambi Province.